Tingkat Kooperatif Penasihat Hukum Kasus Kopi Mirna Dilihat dari Sudut Pandang Strategi Komunikasi - Fitro, Joko; Purnomo, Hadi (CT. Rajawali media Utama, 2024)
The case of Mirna's coffee is a murder case that occurred at Café Olivier in Central Jakarta on January 6, 2016. In this case, Jessica Kumala Wongso was convicted and sentenced to 20 years in prison. During the trial, the cooperative level of Jessica's legal advisors, Otto Hasibuan and Miryam S. Hutagalung, became one of the factors influencing the trial outcome. This article aims to analyze the cooperative level of Jessica's legal advisors from the perspective of communication strategy. The analysis is conducted using the communication strategy theory proposed by Gerbner and Gross. The results of the analysis indicate that the cooperative level of Jessica's legal advisors is quite high. This is evident from several communication strategies they employ, including: Open communication strategy: Jessica's legal advisors are transparent in conveying information to the public. They often hold press conferences to explain the case's developments. Persuasive communication strategy: Jessica's legal advisors attempt to influence public opinion in support of Jessica. They frequently use legal arguments to defend Jessica. Defensive communication strategy: Jessica's legal advisors strive to protect Jessica from accusations directed at her. They often refute these accusations with evidence they possess. In conclusion, Jessica's high cooperative level of legal advisors positively influences the trial outcome. The public supporting Jessica becomes more confident in her innocence, trusting her legal advisors.